2015
DOI: 10.1007/s11606-015-3540-y
|View full text |Cite
|
Sign up to set email alerts
|

Two Randomized Controlled Pilot Trials of Social Forces to Improve Statin Adherence among Patients with Diabetes

Abstract: BACKGROUND:Medication nonadherence is an important obstacle to cardiovascular disease management. OBJECTIVE: To improve adherence through real-time feedback based on theories of how social forces influence behavior. DESIGN: Two randomized controlled pilot trials called PROMOTE and SUPPORT. Participants stored statin medication in wireless-enabled pill bottles that transmitted adherence data to researchers. PARTICIPANTS: Adults with diabetes and a history of low statin adherence based on pharmacy refills (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Unfortunately, participants in neither arm significantly improved their adherence during the trial. This negative finding may be in part due to selection bias given the low percentage of invited individuals who actually enrolled [29••]. Future trials need to clarify our ability to “motivate” greater medication adherence.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…Unfortunately, participants in neither arm significantly improved their adherence during the trial. This negative finding may be in part due to selection bias given the low percentage of invited individuals who actually enrolled [29••]. Future trials need to clarify our ability to “motivate” greater medication adherence.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…impact on patient adherence [37]. One study compared a weekly email reporting system summarizing the patient's adherence to participants receiving no email alerts.…”
Section: Reese Et Al Investigated Two Social Interventions and Theirmentioning
confidence: 99%
“…[16][17][18] Behavioral economics has shown that social forces can also motivate people to engage in beneficial actions like medication adherence, but these approaches are not well-studied. [19][20][21][22] In this study, we investigated the role of social support, in the form of suggesting participants enlist a medication adherence partner (MAP); the effect of alerting patients about their failure to adhere; and the combination of these two interventions.…”
Section: Introductionmentioning
confidence: 99%